Dennell R. W. European Economic Prehistory: A New Approach - Колєсніков, М.I. (Археологія, 1989)
Рецензія на книгу: Dennelt R.W. European Economic Prehistory: A New Approach. — London: Academic Press, 1985. — 217 p.